Extracorporeal shockwave lithotripsy in the management of urinary stones: New concepts and techniques to improve outcomes - Pilar Bahilo-Mateu; Alberto Budia-Alba (Asian Journal of Urology)
Objective: Extracorporeal shockwave lithotripsy (SWL) currently plays an important role in the treatment of urinary tract lithiasis. The purpose of this article was to describe new concepts and procedural strategies that would improve results using SWL as a treatment for urolithiasis, thereby achieving better clinical practice. Methods: A systematic review process was carried in PubMed/PMC from January 2003 to March 2023. A narrative synthesis of the most important aspects has been made. Results: The important recommendations for the adequate selection of the candidate patient for treatment with SWL are summarized, as well as the new strategies for a better application of the technique. Aspects about intraoperative position, stone localization and monitoring, analgesic control, machine and energy settings, and measures aiming at reduced risk of complications are described. Conclusion: To achieve the therapeutic goal of efficient stone disintegration without increasing the risk of complications, it is necessary to make an adequate selection of patients and to pay special attention to several important factors in the application of treatment. Technological development in later generation devices will help to improve current SWL results.